2016
DOI: 10.1007/s11255-016-1354-4
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral renal cancers: oncological and functional outcomes

Abstract: In patients with bilateral renal carcinomas, the histologic concordance was 93.6 %. The bilateral partial nephrectomies or unilateral nephrectomy and contralateral resection provided acceptable oncological and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…It is more difficult to establish AS protocols for patients with multifocal SRMs than for patients with solitary SRMs. Indeed, there is no consensus in this regard in urological guidelines, and there is scarce literature about the clinical behavior of these masses, with only short series having been evaluated [63][64][65][66]. However, there is a real increase in the prevalence of multifocal renal tumors [67].…”
Section: Multifocal Small Renal Masses and Active Surveillancementioning
confidence: 99%
“…It is more difficult to establish AS protocols for patients with multifocal SRMs than for patients with solitary SRMs. Indeed, there is no consensus in this regard in urological guidelines, and there is scarce literature about the clinical behavior of these masses, with only short series having been evaluated [63][64][65][66]. However, there is a real increase in the prevalence of multifocal renal tumors [67].…”
Section: Multifocal Small Renal Masses and Active Surveillancementioning
confidence: 99%
“…They reported significant postoperative renal function deterioration (44.8% eGFR decrease for synchronous (mostly RN → PN) and 30.4% decrease for metachronous tumor (all RN → PN) after the second operation, respectively), but hemodialysis was rarely required. Compared to their results, we showed more eGFR preservation if RN → PN (23.1% decrease) is performed respectively even though their cohort characteristics are slightly different [ 32 ].…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, we reported the CSS difference between synchronous bilateral renal cancer group and metachronous bilateral renal cancer group. And in previous studies, Csaba Berczi showed that the 5-year CSS were 86% in synchronous bilateral renal cancer while 75% in metachronous group [4]. Singer EA showed that overall survival was 88% and CSS was 97% after a minimum of 10-year follow-up for patients with bilateral renal cancer [5].…”
Section: Discussionmentioning
confidence: 87%